Study of tongue-palate pressure patterns during the hold phase in the production of French denti-alveolar and velar stops. (1st February 2020) - Mirchandani, Bharat; Perrier, Pascal; Grosgogeat, Brigitte; Jeannin, Christophe
ABSTRACT: The hold phase of the stop consonants is crucial for a successful production of the release and the acoustic burst. Concurrently, it is also associated with weak acoustic energy and minimal movement, so that conventional acoustic and kinematic approaches are not relevant to investigate motor control. This paper presents an innovative experimental method to study speech motor control during this phase, based on meticulous measurement of the time variation of the mechanical pressure exerted by the tongue against the palate and also characterizing tongue–palate interaction. The concept is based on using miniature transducers with enhanced response characteristics inserted in different locations of the complete denture of edentulous subjects without perturbing the articulation. The study was done with a French-speaking adult whose maxillary denture was duplicated and mounted with six strain gauge transducers. The experiment was done with denti-alveolar and velar stop consonants with two vowel contexts. The results illustrate the potential of such device to analyse speech motor control when contact constrains tongue movements.